Analisis Pemanfaatan Geogebra dalam Meningkatkan Pemahaman Konsep Volume Tabung - Aurellia, Clarine; Harahap, Rosliana (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2024)
Education is one way to improve the quality of life of the nation. The basis of an education aims to improve the level of thinking of students in making a decision, exploring, creating something to compete at the international, national and other levels. One of the compulsory subjects is mathematics which is an important part of science. Low understanding by students in mastering mathematics is a problem that must be solved. The purpose of this study is to determine and analyze the improvement of students' ability to understand one of the mathematical applications, namely tube volume with the help of geogebra applications. This research uses a descriptive qualitative research approach with a case study approach through observation and document studies by researching at the Private Aliyah Madrasah school Ex. PGA UNIVA Medan Project. Data analysis used in this study through data reduction, data presentation and verification by taking samples of class XI Science 2 with 22 students. The first test is given by explaining the manual and for the second test, explaining the tube volume material with the application of geogebra. The results of this study that the use of the gogebra application as a teaching aid greatly affects the improvement of students in understanding space building lessons, including the volume of tubes with an average value from the pre-test of 65.6818 and the average value of the post test of 84.8636 with a value of Sig. (2-tailed) of 0.000 ? 0.05. This research proves that the geogebra application is very helpful for teachers and students in understanding concepts in terms of images in mathematics.